Civil Liability of Business Actors for Reverse Passing Off as an Unlawful Act - Putri, Nur Zahra Magriba; Sulastri, Sulastri (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This research aims to determine the civil liability of business actors who commit Reverse Passing Off by analyzing the legal arrangements regarding Reverse Passing Off from the perspective of Indonesian positive law. This research uses a normative juridical method focusing on legal issues relating to Reverse Passing Off. This research uses a statutory and conceptual approach with data collection techniques, using literature study through normative qualitative analysis methods. The results show that the Trademark Law in Indonesia does not explicitly regulate legal arrangements related to Reverse Passing Off. Still, the principles of consumer protection and provisions on unlawful acts can be used as a basis for handling this practice. Business actors who commit this act must be legally responsible, and the original trademark owner has the right to claim both material and immaterial damages. Alternatively, the resolution of this problem can be done through mediation with the results of mediation in the form of a written agreement that contains legal responsibility and protection for the trademark owner. Therefore, there is a need for regulatory reform, especially in trademark law, by adding reverse passing off as a trademark infringement to protect the aggrieved party and ensure legal certainty, fairness, and transparency in trade.